The Demand for Money and For Consumption Goods in Centrally Planned Economies - Portes, Richard; Winter, David (The Review of Economics and Statistics, 1978)
HIS article gives estimates of household demand for money and savings functions for four centrally planned economies (CPEs). The data are post-war annual time series for Czechoslovakia, the GDR, Hungary, and Poland. The estimation of these functions characterizing the demand side of the consumption goods market is a part of the empirical component of our research into macroeconomic equilibrium in CPEs. The supply side of the consumption goods market is analysed in a separate paper (Portes and Winter, 1977), and we are currently carrying out disequilibrium estimation (Goldfeld and Quandt, 1975) in a model using the demand and supply function specifications developed in these papers. It is conventional wisdom that since the early 1950s, the CPEs have suffered chronically from some significant degree of excess demand (repressed inflation), i.e., that buyers have faced quantity constraints (informal or formal rationing) on the markets for goods and labour (e.g., Bush, 1973; Garvy, 1975; Schroeder, 1975). When authors think it necessary to give empirical justification, this is in the form of reference to queues, shortages, hidden price increases, quality deterioration, excess liquidity and forced saving, and some data on prices in the small free market sectors of these